Relationship Intake Maternal Nutrition in 1000 Days of Life and Infant Nutritional Status at Age Two - Ibrahim, Sitti Hasrah; Irmadani , Andi Syarifah (Advances in Healthcare Research, 2025)
Purpose: This study aims to examine in depth the relationship between maternal nutrition intake during the first 1000 days of life (HPK) and the nutritional status of children at two years of age. The primary focus of this study is to explore the association between adequate intake of essential nutrients such as protein, iron, zinc, folic acid, and vitamin A during pregnancy and child growth indicators, including weight-for-age (WFA), height-for-age (HFA), and weight-for-height (WFA). Research Method: This study employs a qualitative approach, utilizing a systematic literature review method. The review was conducted on various relevant studies published between 2015 and 2025, which addressed the biological, socioeconomic, and health intervention dimensions related to maternal nutrition and its impact on the nutritional status of two-year-old children. The analysis was conducted thematically by grouping the findings into six main discussion areas. Results and Discussion: The results show a strong association between maternal nutritional adequacy and child growth at the age of two years. Factors such as nutritional imbalance during pregnancy, maternal education level, local dietary culture, and the quality of maternal and child health services play important roles. Systematic and contextually appropriate nutrition intervention programs are urgently needed to optimize child growth outcomes. Implications: This study makes a significant contribution to the development of maternal and child health policies and can serve as a basis for planning community-based and cross-sectoral interventions aimed at preventing stunting.